Impact of Hemodialysis Catheter Dysfunction on Dialysis and Other Medical Services: An Observational Cohort Study. (12th February 2012) - Griffiths, Robert I.; Newsome, Britt B.; Leung, Grace; Block, Geoffrey A.; Herbert, Robert J.; Danese, Mark D.
Abstract : Practice guidelines define hemodialysis catheter dysfunction as blood flow rate (BFR) <300 mL/min. We conducted a study using data from DaVita and the United States Renal Data System to evaluate the impact of catheter dysfunction on dialysis and other medical services. Patients were included if they had ≥8 consecutive weeks of catheter dialysis between 8/2004 and 12/2006. Actual BFR <300 mL/min despite planned BFR ≥300 mL/min was used to define catheter dysfunction during each dialysis session. Among 9, 707 patients, the average age was 62, 53% were female, and 40% were black. The median duration of catheter dialysis was 190 days, and the cohort accounted for 1, 075, 701 catheter dialysis sessions. There were 70, 361 sessions with catheter dysfunction, and 6, 33 1 (65.2%) patients had at least one session with catheter dysfunction. In multivariate repeated measures analysis, catheter dysfunction was associated with increased odds of missing a dialysis session due to access problems (Odds ratio [OR] 2.50; P < 0.001 ), having an access-related procedure (OR 2.10; P < 0.001 ), and being hospitalized (OR 1.10; P = 0.001 ). Catheter dysfunction defined according to NKF vascular access guidelines results in disruptions of dialysis treatment and increased use of other medical services.